Efficiency of Trained Farmers on the Productivity of Broilers in a Selected Area of Bangladesh - Ershad, S.M.E.; Islam, S.S.; Mondal, S.C.; Sarkar, B. (International Journal of Poultry Science, 2004)
The study was conducted in Jessore District of Bangladesh to observe the efficiency of trained farmers as compared to farmers with out training on the production performances of broilers as well as the net profit from broiler production. Three categories of farmers were considered in the present study, viz., Certificate on Livestock and Poultry (CLP) trained farmers, this category of farmers had 6 months long training on livestock and poultry production, Youth Training Center (YTC) trained farmers, this category of farmers had 3 months long training on livestock and poultry production and General farmers, this category of farmers had no formal training on poultry/broiler production. The production parameters considered in the study were live weight gain (kg bird-1), feed consumption (kg bird-1), feed conversion ratio (FCR) and mortality (%). The overall production performances and net profit was found better in both of the trained farmers categories as compared to general farmers. Therefore, it can be recommended here that the training of farmers is obvious for efficient and profitable broiler production in the country.